Functional Characterization of Stromal Osteopontin in Melanoma Progression and Metastasis - Kumar, Santosh (Public Library of Science, 2013)
BACKGROUND: Recent studies demonstrated that not only tumor derived- but stroma derived factors play crucial role in cancer development. Osteopontin (OPN) is a secreted non-collagenous, sialic acid rich, chemokine-like phosphoglycoprotein that facilitates cell-matrix interactions and promotes tumor progression. Elevated level of OPN has been shown in melanoma patient and predicted as a prognostic marker. Recent reports have indicated that stroma-derived OPN are involved in regulating stem cell microenvironment and pre-neoplastic cell growth. However, the function of stroma derived OPN in regulation of side population (SP) enrichment leading to melanoma growth, angiogenesis and metastasis is not well studied and yet to be the focus of intense investigation. METHODOLOGY/PRINCIPAL FINDINGS: In this study, using melanoma model, in wild type and OPN knockout mice, we have demonstrated that absence of host OPN effectively curbs melanoma growth, angiogenesis and metastasis. Melanoma cells isolated from tumor of OPN wild type (OPN(+/+)) mice exhibited more tumorigenic feature as compared to the parental cell line or cells isolated from the tumors of OPN KO (OPN(−/−)) mice. Furthermore, host OPN induces VEGF, ABCG2 and ERK1/2 expression and activation in B16-WT cells. We report for the first time that stroma derived OPN regulates SP phenotype in murine melanoma cells. Moreover, loss in and gain of function studies demonstrated that stroma-derived OPN regulates SP phenotype specifically through ERK2 activation. CONCLUSIONS: This study establish at least in part, the molecular mechanism underlying the role of host OPN in melanoma growth and angiogenesis, and better understanding of host OPN-tumor interaction may assist the advancement of novel therapeutic strategy for the management of malignant melanoma.